African Jurisprudence as Historical Co-extension of Diffused Legal Theories - (:unkn) unknown (My University, 2022)
African jurisprudence, like African philosophy, continues to be hotly debated. This article contends that the debate straddles the uniqueness claim which either emphasises the existence or possibility of a peculiar legal framework on the continent, and a historical co-extensional position reiterating that African jurisprudence is a continuum of other legal traditions. The article argues that there is no uniquely African jurisprudence, and that what obtains within the structures of jurisprudence on the continent also exists within various legal traditions elsewhere, and as such can at best be described as ‘jurisprudence in Africa’ rather than ‘African jurisprudence’. It defends this thesis through analytic and comparative explications of the content of natural law theory and legal positivism as experienced on the continent. It concedes that relics of the colonial legal experience create contestations that inform scholars’ calls for a return to traditional legal systems. It concludes that a reconstructive jurisprudence in Africa must take cognisance of the continent’s historical and evolutionary legal experiences, but that a unified or monolithic theory may not be sufficient to address the choice of functional jurisprudence.
Keywords: African Research